Endothelial Dysfunction and Endocan Levels in Patients with Gilbert Syndrome and Moderate Hyperbilirubinemia. (November 2022) - Zengin, Oguzhan; Sahiner, Enes Seyda; Inan, Osman; Topcuoglu, Canan; Turhan, Turan; Altiparmak, Emin; Yilmaz, Nisbet; Ates, Ihsan
In this study, we aim to evaluate the presence of endothelial dysfunction in Gilbert syndrome patients with left ventricular mass index (LVMI) and endocan levels. The study included 60 patients who diagnosed with Gilbert syndrome and 60 healthy controls who did not have any known diseases. Human endocan levels were measured using a sandwich ELISA method. The endocan and LVMI levels were lower in the Gilbert syndrome group than in the healthy controls. In the Gilbert syndrome group, total bilirubin level was negatively correlated with LVMI (r = −0246; P = .007) and endocan levels (r = −.270; P = .046). In the Gilbert syndrome group, increasing age (β ± SE = 20.78 ± 7.47; P = .006), was a positive independent predictor of LVMI, and increasing high-density lipoprotein cholesterol (HDL-C) (β ± SE = −.27 ± .09; P = .007), and total bilirubin levels (β ± SE = −6.09 ± 3.02; P = .046) were found to be a negative independent predictor. These results support that endothelial dysfunction is decreased in Gilbert Syndrome patients with mild hyperbilirubinemia compared with the healthy control group.